The Effect Of Green Bean Flour Substitution On The Quality Of Snow's Cookies - Amimy, Findi; Syarif, Wirnelis (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research is motivated by the lack of utilization of local food ingredients, especially mung bean flour in food processing. Because usually the main ingredient for making Snow White cookies uses imported ingredients, namely flour. This study aims to analyze the effect of 0%, 25%, 50% and 75% substitution of mung bean flour on the quality of snow white cookies in terms of shape, color, aroma, texture and taste. This type of research is a pure experiment (true experiment) using One-factor completely randomized design (CRD) method, namely the use of mung bean flour (0%, 25%, 50% and 75%) with three repetitions. The type of data used is primary data sourced from 3 expert panelists who have provided an assessment through a questionnaire (organoleptic test format). The data that has been obtained are then tabulated and analysis of variance (ANOVA) is performed. If they are different and there is an effect, the Duncan test is carried out. The results showed that there was a significant effect between 0%, 25%, 50% and 75% on the quality of Snow White's cookies, namely the quality of the inner color, the fragrant aroma of green beans and the taste of green beans. The quality of the crescent shape, neat, crumbly texture and sweet taste had no effect on the quality of Snow White's cookies. The best percentage of quality in the inner color was obtained at 50% substitution, the fragrant aroma of the substituted green beans was 75% and the taste of green beans was 75%.